2012
DOI: 10.1159/000341857
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Predicts Long-Term Motor Functional Outcome in Patients with Acute Supratentorial Intracranial Hemorrhage

Abstract: Background/Aim: It remains unclear how wallerian degeneration of the pyramidal tract (PT) in the acute phase of supratentorial intracranial hemorrhage (ICH) correlates with the long-term functional outcome. The aim of this study was to quantify and predict the long-term neuromotor outcome using diffusion tensor imaging (DTI) during the early stages of ICH. Methods: Twenty-seven patients with a hemiparetic ICH were prospectively studied using DTI either within 3 days or at 2 weeks after onset. A region-of-inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 49 publications
4
23
0
Order By: Relevance
“…The timing of the MRI being performed and clinical outcome evaluation are comparable with those of previously published reports, but we were able to recruit more cases than previous studies. 9,10,16 In addition, this is the first report to evaluate the relationship between the FA ratio in four different areas along the CST and motor outcomes after ICH, and the results may imply the value of microstructural change over the CST. However, further investigations are necessary to clarify the fibre change in an injured CST after ICH.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The timing of the MRI being performed and clinical outcome evaluation are comparable with those of previously published reports, but we were able to recruit more cases than previous studies. 9,10,16 In addition, this is the first report to evaluate the relationship between the FA ratio in four different areas along the CST and motor outcomes after ICH, and the results may imply the value of microstructural change over the CST. However, further investigations are necessary to clarify the fibre change in an injured CST after ICH.…”
Section: Discussionmentioning
confidence: 86%
“…[13][14][15] Most previous studies have used only the cerebral peduncle as the ROI for FA and ADC measurements to predict motor outcomes. 9,10,16 Our study is unique in that we assessed four sites along the CST, to measure DTI indices including the corona radiata, perihaematomal oedema area, cerebral peduncle and pons. Different from previous studies, this showed that injured CST could change during the motor recovery stage among patients with ICH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study by Wang et al 48 showed a comparable relationship with fractional anisotropy and independence of hematoma size, but also found that there may be differing diagnostic value when DTI is performed in the acute (3 days postictus) and subacute (2 weeks postictus) periods in hemiparetic patients. When DTI was performed in the subacute period, it was found to be more predictive of motor and functional outcome.…”
Section: Prognostication After Ichmentioning
confidence: 64%
“…A signiicant inding being that fractional anisotropy ratio did not correlate to size of the bleed but did correlate with recovery [17], which could serve as an important tool for the prediction of recovery post ICH. The predictive value of these studies has shown to be higher when carried out subacutely (2 weeks) rather than acutely (3 days) after the bleed which may be accounted for by the resolution of acute injury and inlammation and onset of repair and compensation [18]. Functional MRI (fMRI) is being evaluated as a means to evaluate the extent of injury and functional deicit post ICH based on functional connectivity rather than just a structural basis, with fMRI possibly evaluating the activity between physical and functional connections.…”
Section: Detecting Etiologymentioning
confidence: 99%